2017
DOI: 10.1002/jsfa.8293
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of multiple mycotoxins and other fungal metabolites in animal feed and maize samples from Egypt using LC‐MS/MS

Abstract: According to the international standards, the contamination rates in the investigated regions were not alarming, except for AFB1 in maize. The necessity of further and continuous monitoring is highly recommended to establish a database for mycotoxin occurrence. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 41 publications
9
84
0
Order By: Relevance
“…ALLAMEH et al (2005) also observed that using corn containing 1,000μg/kg of AFB 1 as ingredient resulted in the concentration of 650μg/kg in the feed. A similar reduction in the frequency of positive samples was reported in a study conducted in Egypt by ABDALLAH et al (2017), who detected AFB 1 in 16% of corn and 4% of feed samples analyzed, at mean levels of 4.8 and 5.3μg/kg, respectively. In our study, the frequencies and levels of AFs were similar in freshly prepared feed and feed available in the farms, thus indicating good storage conditions of feed in the farms evaluated.…”
Section: Resultssupporting
confidence: 85%
“…ALLAMEH et al (2005) also observed that using corn containing 1,000μg/kg of AFB 1 as ingredient resulted in the concentration of 650μg/kg in the feed. A similar reduction in the frequency of positive samples was reported in a study conducted in Egypt by ABDALLAH et al (2017), who detected AFB 1 in 16% of corn and 4% of feed samples analyzed, at mean levels of 4.8 and 5.3μg/kg, respectively. In our study, the frequencies and levels of AFs were similar in freshly prepared feed and feed available in the farms, thus indicating good storage conditions of feed in the farms evaluated.…”
Section: Resultssupporting
confidence: 85%
“…Kojic acid (KA) is a secondary fungal metabolite of many species of Aspergillus, Acetobacter, and Penicillium (Burdock, Soni, & Carabin, 2001). In this survey, KA occurred in less than half of the samples (43%) at higher levels than those reported previously in other commodities such as maize (5357 μg/kg) and groundnut (485 μg/kg) from Nigeria (Kayode et al, 2013), maize from Brazil (1719 μg/kg) (Oliveira, Rocha, Sulyok, Krska, & Mallmann, 2017) and maize from Egypt (25040 μg/kg) (Abdallah, Girgin, Baydar, Krska, & Sulyok, 2017). The detection of KA has not been detected in dates or in any other dried fruits before.…”
Section: Occurrence Of the Nonregulated Mycotoxins And Other Fungal Mmentioning
confidence: 72%
“…Several reports have documented the high frequencies of emodin and physcion in different agricultural crops. The rest of these metabolites are unspecific and have been previously detected along with AFs in other food and feed commodities from Egypt (Abdallah et al, 2017;Abdallah, Krska, & Sulyok, 2016).…”
Section: Occurrence Of the Nonregulated Mycotoxins And Other Fungal Mmentioning
confidence: 99%
“…Deoxynivalenol, zearalenone, and fumonisins are produced by Fusarium species, whereas ochratoxins are produced by several species of Aspergillus . Several reports have described mycotoxicoses outbreaks as a result of mycotoxin contamination; therefore, maintaining a safe supply of food and feed for both human and animal consumption is a critical issue . Aflatoxin B 1 (AFB1) is the most potent natural product.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several reports have described mycotoxicoses outbreaks as a result of mycotoxin contamination; therefore, maintaining a safe supply of food and feed for both human and animal consumption is a critical issue. 6 Aflatoxin B 1 (AFB1) is the most potent natural product. It is classified as a group A carcinogen, whereas ochratoxin A (OTA) is classified as group 2B (a possible human carcinogen), and there is no adequate information about patulin carcinogenicity, which consequently is classified as group 3 on the International Agency for Research on Cancer (IARC) classification.…”
Section: Introductionmentioning
confidence: 99%